EARLY TRIASSIC CONCHOSTRACANS from the TIRYAKHKOBYUME SECTION (SOUTHERN VERKHOYANSK REGION, REPUBLIC of SAKHA (YAKUTIA)) - Zharinova V.V.; Scholze F.; Davydov V.I.; Kutygin R.V. (2020)
© 2020 Kazan Federal University. All rights reserved. Conchostracans (Crustacea) from the Induan deposits of the Tiryakh-Kobyume section (southern Verkhoyansk region) were studied. We identified the following seven conchostracan species belonging to five genera: Pseudestheria Raymond, 1946; Euestheria Deperet et Mezeran, 1912; Sphaerestheria Novojilov, 1954; Lioestheria Deperet et Mezeran, 1912; Wetlugites Novojilov, 1958. Most of the previously identified species in the Tiryakh-Kobyume region (“Pseudestheria sibirica”, “Ps. tumaryana”, “Ps. kashirtzevi”, and “Sphaerestheria aldanensis”) were described in the middle of the 20th century from the basal Triassic in the western Verkhoyansk region (Balbuk section). Revision of these species with the use of modern methods of conchostracan classification is needed.